Human resource management practices and organizational outcomes in the accommodation facilities in central philippines - Tayco, Ryan Olindo (Institut Pariwisata dan Bisnis Internasional, 2022)
HRM practices are management tools that contribute to the success of an organization. This study investigates the HRM practices and organizational outcomes in the accommodation facilities in Central Philippines using correlational research. 805 total participants answered the survey questionnaires were 123 are supervisors/managers and 682 are from the personnel of the accommodation facilities. The results showed that the respondents were satisfied with the HRM practices in the accommodation facilities where they are working. All provinces in Central Philippines, the type of accommodation facilities, and participants by generation moderately agreed that the accommodation facilities they are working in have excellent HRM practices. In terms of organizational outcomes, the accommodation facilities experience minor turn-over and absenteeism rates of their employees, a good level of productivity, substantially above average goals, and higher profit/surplus on their financial performance. The researcher concluded that there is a relationship between HRM practices and organizational outcomes that accommodation facilities that implement favorable HRM practices are more likely to have positive organizational outcomes. Higher levels of HRM practices are associated with higher organizational outcomes.